2013
DOI: 10.1002/smj.2085
|View full text |Cite
|
Sign up to set email alerts
|

Fast-mover advantages: Speed capabilities and entry into the emerging submarket of atlantic basin LNG

Abstract: International audienceEntry timing benefits and costs typically vary with firms' capabilities. In this study, we empirically examine the entry timing implications of firms' intrinsic speed capabilities, which refer to the ability to execute investment projects faster than competitors. We hypothesize that firms with intrinsic speed capabilities face low preemption risks and, thus, can afford to wait longer for uncertainty resolution before deciding to enter new markets. This hypothesis is more applicable when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 53 publications
4
75
0
2
Order By: Relevance
“…First mover advantages (i.e., the leadership position gained by the initial occupant of a market) have been shown to provide long-term benefits to those organizations that enter and exploit new markets earlier than potential competitors (Gort and Klepper, 1982; Glazer, 1985). In some circumstances, speed might even be more beneficial than technical performance per se (Eisenhardt, 1989; Brusoni et al, 2007; Hawk et al, 2013). However, it is clearly optimal to maintain both quality and speed in the decision-making process (Yu et al, 2011; Tzovara et al, 2012; Symmonds et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…First mover advantages (i.e., the leadership position gained by the initial occupant of a market) have been shown to provide long-term benefits to those organizations that enter and exploit new markets earlier than potential competitors (Gort and Klepper, 1982; Glazer, 1985). In some circumstances, speed might even be more beneficial than technical performance per se (Eisenhardt, 1989; Brusoni et al, 2007; Hawk et al, 2013). However, it is clearly optimal to maintain both quality and speed in the decision-making process (Yu et al, 2011; Tzovara et al, 2012; Symmonds et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Those real option papers looking at operation management issues include studies investigating the expansion/divestment of existing operations (e.g., Kogut, ; Folta and Miller, ; Xu et al, ), as well as the entry into new industries (Campa, ; Folta and O'Brien, ; Hawk et al, ). Future research might employ real option logic to look at other operation decisions such as those involving product diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on option timing focus on a variety of contexts, including technology or R&D investments (e.g., McGrath and Nerkar, ; Cuervo‐Cazurra and Un, ) as well as timing of investments in new markets and new products (e.g., Folta and O'Brien, ; Hawk et al, ) and highlight factors that prompt (e.g., technical experience, existence of numerous competitors) or deter investments (e.g., market uncertainty).…”
Section: A Model Of Real Option Decision‐makingmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of how firms overcome these challenges and reduce the risk of failure to enter into new product markets is an important one. Despite its importance, very little research exists on pre‐entry, i.e., the period leading up to actual product market entry (see Hawk et al, for a recent exception). In a recent review of the market entry literature, scholars have concluded that the prior studies tend to portray entry as an event (Zachary et al, ), and they have called for more research that examines what happens prior to entry.…”
Section: Introductionmentioning
confidence: 99%